Transcriptome Analysis During Follicle Development in Turkey Hens With Low and High Egg Production - Brady, Kristen; Liu, Hsiao-Ching; Hicks, Julie A.; Long, Julie A.; Porter, Tom E. (Frontiers in Genetics, 2021)
Low egg producing hens (LEPH) and high egg producing hens (HEPH) exhibit gene expression differences related to ovarian steroidogenesis. HEPH display increased expression of genes involved in progesterone and estradiol production, in the granulosa layer of the largest follicle (F1G) and small white follicles (SWF), respectively, whereas LEPH display increased expression of genes related to progesterone and androgen production in the granulosa (F5G) and theca interna layer (F5I) of the fifth largest follicle, respectively. Transcriptome analysis was performed on F1G, F5G, F5I, and SWF samples from LEPH and HEPH to identify novel regulators of ovarian steroidogenesis. In total, 12,221 differentially expressed genes (DEGs) were identified between LEPH and HEPH. Pathway analysis inferred differential regulation of the hypthalamo-pituitary-thyroid (HPT) axis, particularly thyroid hormone transporters and thyroid hormone receptors, and of estradiol signaling in LEPH and HEPH. The HPT axis showed up-regulation in HEPH in less mature follicles but up-regulation in LEPH in more mature follicles. Estradiol signaling exclusively exhibited up-regulation in HEPH. Treatment of SWF cells from LEPH and HEPH with thyroid hormone in vitro decreased estradiol production from HEPH cells to the levels seen in LEPH cells, whereas thyroid hormone treatment did not impact estradiol production in LEPH cells. Transcriptome analysis of the major cell types involved in steroidogenesis inferred the involvement of the HPT axis and estradiol signaling in the regulation of differential steroid hormone production seen among hens with different egg production levels.